Influence of nano-encapsulated Yucca schidigera extract on ruminal anaerobic gases of methane, carbon monoxide, and hydrogen sulfide production of different carbohydrate-based diets - Edwin Oswaldo Botia Carreño; Tonantzin Díaz Alvarado; Jorge Alfonso Diego Acosta; Pedro Enrique Hernández Ruiz; Mona M.M.Y. Elghandour; Oluwagbemiga A. Dada; Maximilian Lackner; Abdelfattah Z.M. Salem (Journal of Agriculture and Food Research)
Saponins, the primary components of Yucca schidigera extract (YSE), are known to influence microbial activity in the rumen, which can affect various fermentation parameters. Moreover, encapsulating YSE with chitosan (CS) at varying carbohydrate levels (CHO) adds another layer of complexity that can provide valuable insights into the use of additives in mitigating greenhouse gases. This study investigated the impact of both crude and encapsulated forms of YSE on the production of ruminal anaerobic gases in cattle fed different levels of CHO-based diets. Ruminal contents were obtained from four slaughtered, crossbreed bulls (Charollais × Limousin) with a live weight of 400 ± 25 kg. The experimental design followed a completely randomized factorial arrangement, with factors including CHO level (25 %, 45 %, and 55 % DM), YSE forms (without extract, CS, crude, and nano-capsules), and dose of extract (0-, 0.25-, 0.5- and 1.0- mL/g of DM). Results showed that the type of extract significantly affected asymptotic total gas production, methane (CH4), hydrogen sulfide (H2S), carbon monoxide (CO), and dry matter digestibility. Nano-chitosan increased gas production and exhibited greater efficiency in reducing CH4 production by up to 61.4 %. While crude YSE reduced CH4 production by 38 %, nano-capsules increased production by 17.7 %–42.8 %. Furthermore, a significant interaction effect among CHO levels, type of extract, and extract dose was observed, particularly impacting H2S and CH4 production after 48 h of incubation, alongside an increase of about 25.3 % in metabolizable energy compared to the control. The use of CS and YSE improved (p < 0.0001) the CH4 conversion efficiency by 71.3 % and 23.4 % respectively, and at some point, the encapsulation of YSE resulted in a significant reduction in efficiency by up to about 49.5 %. The study concluded that both CS and YSE have the potential to enhance digestibility in cattle and reduce CH4 production and its conversion efficiency. However, encapsulating YSE with CS may reduce the efficiency of either compound in optimizing ruminal fermentation, unless other influencing factors are carefully considered. Therefore, the optimal efficacy of nano-encapsulated YSE depends on finding a balance between extract type, dosage, and dietary CHO level.